2013
DOI: 10.1177/003335491312800309
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Vision Screening in Primary Care Pediatric Practice

Abstract: Objectives. We determined the efficacy of pediatric-based preschool vision screening, as knowledge of vision screening effectiveness in primary care pediatrics is incomplete.Methods. Pediatricians and staff at nine primary care pediatric practices were trained in vision screening, and practices screened children aged 3-5 years from May 2007 through July 2008. Children failing or considered untestable were referred for pediatric ophthalmology examinations. We determined rates of testability, failure, referral, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
4
14
0
Order By: Relevance
“…Using HOTV optotypes, overall sensitivity found by the VIP group was 54%, 18 with which the JVAS again compares favorably. In a study of visual acuity screening using a Lea symbol chart, 19 the PPV was found to be 66.7%, similar to our PPV result of 66% to 79% (Table 3). Although JVAS sensitivity appears higher than sensitivities found for visual acuity tests in the VIP studies, it is difficult to compare directly results when there are differences between studies regarding primary care versus enriched populations, ages of subjects, screening pass/fail thresholds, and the gold standard criteria used.…”
Section: Discussionsupporting
confidence: 87%
“…Using HOTV optotypes, overall sensitivity found by the VIP group was 54%, 18 with which the JVAS again compares favorably. In a study of visual acuity screening using a Lea symbol chart, 19 the PPV was found to be 66.7%, similar to our PPV result of 66% to 79% (Table 3). Although JVAS sensitivity appears higher than sensitivities found for visual acuity tests in the VIP studies, it is difficult to compare directly results when there are differences between studies regarding primary care versus enriched populations, ages of subjects, screening pass/fail thresholds, and the gold standard criteria used.…”
Section: Discussionsupporting
confidence: 87%
“…Using HOTV optotypes, overall sensitivity found by the VIP group was 54%, 18 with which the JVAS again compares favorably. In a study of visual acuity screening using a Lea symbol chart, 19 the PPV was found to be 66.7%, similar to our PPV result of 66% to 79% (Table 3). Although JVAS sensitivity appears higher than sensitivities found for visual acuity tests in the VIP studies, it is difficult to compare directly results when there are differences between studies regarding primary care versus enriched populations, ages of subjects, screening pass/fail thresholds, and the gold standard criteria used.…”
Section: Discussionsupporting
confidence: 87%
“…Even if the GSE is free, parents must take time off work to appear for the appointment, and they may not be aware-even in the case of a failed screening-of the importance of early detection and treatment of amblyopia and strabismus. Overall, our completed GSE rate was comparable with that in other published studies, 17,[21][22][23] and there was no reason to assume that any systematic errors could have led to bias in the patients who did receive GSE. Although we cannot know whether the children who did not attend the GSE had amblyopia or strabismus, our finding of 1 of 102 children (1%) who completed the GSE affected with amblyopia is consistent with the published prevalence of 2.5%.…”
Section: Discussionsupporting
confidence: 85%
“…22 Considering the expected low attendance at the GSE, and further considering that most families in the present study would not have the imperative of a screening failure referral to motivate them to take the time to schedule the GSE, it was anticipated that only 20%-40% of patients would obtain the GSE and that screening of up to 300 patients would be required to achieve the desired sample size of 100 children with completed GSEs.…”
Section: Author Manuscript Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation